2015
DOI: 10.1017/s0033291715000884
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of post-traumatic stress disorder symptoms among adolescents after the Wenchuan earthquake in China

Abstract: Adolescents' PTSD symptoms showed an anniversary reaction. Although many adolescents remain euthymic or recover over time, some adolescents, especially those with the risk factors noted above, exhibit chronic, delayed or relapsing symptoms. Thus, the need for individualized intervention with these adolescents is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
168
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(193 citation statements)
references
References 38 publications
16
168
3
6
Order By: Relevance
“…Posttraumatic stress disorder (PTSD) is one of the most studied negative outcomes in trauma-focused research (Fan, Long, Zhou, Zheng, & Liu, 2015; Giannopoulou et al, 2006). Youth are at particularly high risk of being exposed to traumatic events (Lieberman & Van Horn, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) is one of the most studied negative outcomes in trauma-focused research (Fan, Long, Zhou, Zheng, & Liu, 2015; Giannopoulou et al, 2006). Youth are at particularly high risk of being exposed to traumatic events (Lieberman & Van Horn, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fan et al (2015) found that 65.3% adolescent survivors may show no adverse psychological outcomes. One study found that 72.5% of adolescent survivors showed no depression after the Wenchuan earthquake (Ye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have shown that psychological morbidity decreases over time following natural disasters (Eksi & Braun, 2009; Fan et al, 2015; Piyasil et al, 2011), as also shown in our previous study on adults from the same data collection (Hlodversdottir et al, 2016), while other studies do not show significant changes over time (Jia et al, 2013; Thienkrua et al, 2006; Weems et al, 2010) or they show an increase in symptoms (Shaw et al, 1996; Ye et al, 2014). One reason for our findings might be that proper surveillance and psychological support was not implemented immediately for children after the eruption, indicating that children are a particularly vulnerable group that need developmentally appropriate interventions beyond the needs of adults.…”
Section: Discussionmentioning
confidence: 98%
“…Usually, psychological symptoms peak during the first year post-disaster (Eksi & Braun, 2009; Fan, Long, Zhou, Zheng, & Liu, 2015; Piyasil et al, 2011), but some studies indicate that symptoms do not significantly decrease over time (Jia et al, 2013; Thienkrua et al, 2006; Weems et al, 2010). Long-term studies have even found an increase in psychological symptoms years after the disaster (Shaw, Applegate, & Schorr, 1996; Ye, Fan, Li, & Han, 2014).…”
Section: Introductionmentioning
confidence: 99%